Neele. Adriaan. Before Jonathan Edwards: Sources of New England Theology - Lowe, John T. (Jonathan Edwards studies, 2020)
In the period of what is commonly referred to as the “Edwards Renaissance,” much of the published work on Jonathan Edwards has been devoted to his own exegesis, theological inquiries, and legacies in American religious tradition found in Reformed Christian thought and the shaping of Evangelical identity. However, Protestant scholasticism and Reformed orthodoxy of the early modern era has often been the forgotten background in which Edwards’ theological mind operated and from which it emerged